Pattern of Skin Diseases in Children Attending Dermatology Outpatient Department of a Tertiary Care Hospital - Habib, Aamir; Aamir, Reham Binte; Nazeer, Hafsa; Ahmed, Asfa; Ansari, Mohsin Mehmood; Basra, Arslan Ahmed (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the pattern and frequency of skin disorders in children attending Dermatology Department of a Tertiary Care Hospital.Study Design: Cross-sectional study.Place and Duration of Study: Dermatology Department, Combined Military Hospital Bahawalpur, from Mar to Aug 2023.Methodology: Three thousand eight hundred and eleven (3811) children reporting to dermatology outdoor department with skin diseases during the study period were included in this study. All cases were diagnosed by a consultant dermatologist.  Data regarding patient age and sex was collected for each patient. Diseases were categorized into various groups depending on aetiology and cutaneous structure affected by the disease.Results: The mean age of patients was 8.03+4.40 years. Most common diseases were infections (n=1607, 42.2%), followed by parasitic diseases (n=843, 22.1%), dermatitis and eczematous disorders (n=497, 13.0%) and inflammatory dermatoses (n=136(3.6%) in descending order of frequency. Together, these groups comprised 80.1% of total patients (n=3083). Infections and infestations were found in 64.3 % (n=2445).Conclusion: Infections and infestations are the most commonly encountered disease groups. Scabies followed by pyodermas, dermatophytoses and atopic dermatitis were the four commonly encountered paediatric dermatoses in descending order of frequency, accounting for 54.3% of total number of paediatric patients.